Teaching old indicators even more tricks: binding affinity measurements with the guest-displacement assay (GDA). Issue 49 (27th May 2020) - Sinn, Stephan; Krämer, Joana; Biedermann, Frank
Abstract : A simple change has important consequences: the guest-displacement assay (GDA) is introduced which allows for binding affinity determinations of supramolecular complexes with spectroscopically silent hosts and guests. Abstract : A simple change has important consequences: the guest-displacement assay (GDA) is introduced which allows for binding affinity determinations of supramolecular complexes with spectroscopically silent hosts and guests. GDA is complementary to indicator-displacement assay for affinity measurements with soluble components, but is superior for insoluble or for weakly binding guests.